2015
DOI: 10.1007/s12011-015-0261-3
|View full text |Cite
|
Sign up to set email alerts
|

Dyshomeostasis of Serum Oxidant/Antioxidant Status and Copper, Zinc, and Selenium Levels in Elderly Physically Disabled Persons: an AHAP-Based Study

Abstract: The percentage of elderly persons is rapidly growing. Physical disability is one of the main age-related diseases which affect life quality. There are some studies that suggest the oxidative stress and trace elements are involved in physical disability in elderly persons, but the results are inconclusive. Therefore, the aim of this study was to investigate the status of aforementioned parameters in elderly physically disabled patients vs. healthy ones. According to the Katz questionnaire form, 44 subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…There was no difference in serum concentrations of FRAP in patients with oral carcinoma before and after the treatment [ 55 ]. Hyperglycemia leads to lower FRAP values when compared to healthy subjects [ 56 ] and elderly physically disabled patients had lower FRAP values when compared to healthy ones [ 57 ].…”
Section: Frap Assaymentioning
confidence: 99%
“…There was no difference in serum concentrations of FRAP in patients with oral carcinoma before and after the treatment [ 55 ]. Hyperglycemia leads to lower FRAP values when compared to healthy subjects [ 56 ] and elderly physically disabled patients had lower FRAP values when compared to healthy ones [ 57 ].…”
Section: Frap Assaymentioning
confidence: 99%
“…Cp can also promote inflammatory responses through elevated nitric oxide (NO) release and induction of pro‐inflammatory programs mediated by TNF, IL‐1β, cyclooxygenase‐2 (COX‐2), NADPH oxidase, iNOS (inducible nitric oxide synthase) and prostaglandin E 2 (PGE 2 ) (Choo et al , ). The copper plasma concentration is also elevated in patients with diabetes (Khan et al ., ) and physical disability (Younesi et al , ), as well as during aging. Interestingly, a low‐grade inflammatory status, or inflammaging , is an important component of aging‐related diseases (Malavolta et al , ) and systemic inflammation can cause redistribution of micronutrients that includes copper (Han et al , ; Malavolta et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, supplementation of vitamin C and E was found to increase antioxidant enzymes such as superoxide dismutase and glutathione peroxidase . As for metal ions, serum Zn or Se were positively associated with total antioxidant ability in elderly patients with disability . In children with severe cerebral palsy, Schoendorfer et al .…”
Section: Discussionmentioning
confidence: 98%
“…24 As for metal ions, serum Zn or Se were positively associated with total antioxidant ability in elderly patients with disability. 25 In children with severe cerebral palsy, Schoendorfer et al found that serum Zn was well correlated with glutathione reductase or superoxide dismutase activity, particularly in orally fed patients. 26 Although we did not find any significant difference in oxidative stress between food and formula, physicians should pay attention to the fact that most semi-digestive nutritious liquids lack Se.…”
Section: Discussionmentioning
confidence: 99%